NUMERICAL METHODS with CASIO FX-570EX CLASSWIZ CALCULATOR - Tay Kim Gaik; Phang Chang; Phang Piau (2022)
Motivated by our previous books “How to Use Calculator Casio fx-570 MS in Numerical Methods”, “Numerical Methods Using Casio fx-570 ES Calculator” and “Numerical Methods Using Casio fx-570ES PLUS Calculator” which was published in 2006, 2011 and 2017 respectively as well as our “Numerical Method (1.1 Edition)” module which was published in 2005, we have come up with a subsequent edition entitled “Numerical Methods With Casio fx-570EX CLASSWIZ Calculator”. Solving numerical methods using normal calculators can be a dreary task since it involves tedious iteration which may easily lead to careless mistakes. CALC memory in Casio fx-570MS calculator provides 9 variables (A, B, C, D, E, F, X, Y and M), allowing users to input different values for a function or several functions. Once the function has been input, it can be recalled for calculation. This recall ability helps to repeat the tabulation of a sequence of function values which is required in Numerical Methods. As a result, the numerical calculations become much faster and calculation errors are reduced. However, Casio fx-570MS calculator does not have the natural display function (display mathematical expressions like square roots and fractions).